Atorvastatin potentiates the chemosensitivity of human liver cancer cells to cisplatin via downregulating YAP1 - Guo, Liwen (Oncol Lett, 2021)
Atorvastatin is a competitive inhibitor of β-hydroxy β-methylglutaryl-CoA reductase, which is involved in anticancer effects in numerous types of cancer, including in human liver cancer. However, its functions and underlying mechanisms of chemosensitivity in liver cancer remain to be elucidated. The present study investigated the effect of atorvastatin on cisplatin chemosensitivity and its molecular mechanisms, with a focus on the Yes1-associated transcriptional regulator (YAP1) protein. The present study demonstrated that atorvastatin significantly potentiated chemosensitivity to cisplatin in the liver cancer HepG2 and Huh-7 cell lines. Furthermore, cell survival and apoptosis in liver cancer cell lines were analyzed using MTT assay and flow cytometry, respectively. Atorvastatin suppressed HepG2 and Huh-7 cell viability in a dose-dependent manner, similar to cisplatin and paclitaxel. Subtoxic levels of atorvastatin significantly increased cisplatin-induced apoptosis in Huh-7 cells. Atorvastatin-promoted chemosensitivity was predominantly mediated by caspase 3, caspase 9 and poly-(ADP ribose)-polymerase activation, and YAP1 downregulation. Finally, YAP1 overexpression significantly reversed the susceptibility of Huh-7 cells to cisplatin. Overall, the results of the present study suggested the underlying mechanisms of atorvastatin chemosensitivity in inducing liver cancer cell apoptosis via downregulating YAP1 and implicated the potential application of atorvastatin-potentiated chemosensitivity in liver cancer therapy.